Behavioral Skill Training sebagai Solusi dari Adiksi Gadget pada Anak - Mazaya, Nur Widad; Juwita, Dinda Helmi Kayana; Ekaningrum, Ifada Retno; Pratomo, Sigit Adi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Gadget addiction causes children to be less physically active and less skilled in interacting socially. To overcome the impact of this training, this research provides a solution in the form of a behavioral skill technique in the psychology of behaviorism called Behavioral Skill Training (BST). This study uses the method of literature study. The findings in this paper show that BST is effective in dealing with gadget addiction in children based on techniques in BST which include Instruction, Modeling, Rehearsal, and Feedback steps. The BST program can help develop social, emotional, interpersonal, and problem solving skills in children so that they can reduce the level of gadget addiction and improve the quality of life for children as a whole. Support from parents and schools, as well as regular and systematic evaluations need to be considered in the implementation of the BST program. Keyword: Behavioral Skills Training, Gadget Addiction, Children